Monitoring of nutritional status to children by Integrated Healthcare Center as stunting early detection - Ni Ketut Erawati; Wayan Sugandini; Made Juliani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
One of the strategic steps in the effort to deal with stunting nutrition is the use of Integrated Healthcare Center (Posyandu). Posyandu as the front line that can provide information to parents about the nutritional status of children, and Posyandu components that are no less important are cadres. The skills of cadres in determining nutritional status through anthropometric measurements are needed so that they can provide appropriate information for the community, but cadre education activities related to children under five nutrition have not been carried out for a long time. This service is carried out with the aim of providing re-education to cadres on monitoring the nutritional status of children under five through anthropometric measurement methods. The target of this activity is the cadres of the Posyandu in Tegallinggah Village, totaling 15 people. Through counseling and practicing anthropometric measurements, it is hoped that the knowledge and skills of cadres in determining the nutritional status of toddlers will increase. Evaluation of this activity was carried out through pre-test and post-test methods on cadres and the results were obtained after being given refresher on monitoring children under five nutrition, 80% of cadres had knowledge in the good category and 100% of cadres were able to measure Height (TB) and Weight (BB) correctly.